The relationship between duration, stage and, treatment of illness and depression or anxiety in patients with chronic hepatitis B - Karlidag, Gulden Eser; Atmaca, Murad (Cumhuriyet Univ Tip Fak Psikiyatri Anabilim Dali, 2019)
Objective: This study aims to establish in chronic HBV patients the frequency of depression and anxiety, independently from drug side effects, among the antiviral-treated group and the untreated follow-up group and accordingly, to evaluate relationship between the treatment and the factors affecting prevalence of depression and anxiety in these patients. Methods: Included in our study are patients aged between 18 and 60 followed-up and treated for chronic hepatitis B. Three groups were formed in our study: chronic hepatitis group treated with oral antiviral agents (n=103 patients), untreated chronic infection group (n=94 patients) and healthy control group with the same age as treatment group patients (n=50). Factors such as age, sex, education, marital status of the patient, duration of the illness, whether or not the patient is treated, treatment type if treated, history of a prior hepatitis and cirrhosis in family are examined. All participants are scored using Hamilton Anxiety and Hamilton Depression Scales. Results: Two hundred and forty-seven people consisting of 169 males (68.4%) and 78 females (31.6%) were included in this study. No difference was observed in terms of demographical characteristics of all groups. In comparison there among, a statistically significant anxiety and depression score was detected between the chronic infection group on one side and the chronic hepatitis and the control groups on the other side. For participants with a family history of cirrhosis due to chronic HBV, not only anxiety, but also depression scores were detected to be significantly high. Compared to participants with higher education levels, anxiety and depression scores of participants with lower educations levels were determined to be significantly high. Conclusion: This study, the depression and anxiety scores being lower in antiviral treatment group as regards the group treated for chronic infection may be construed as a result of therapeutic effect of antiviral agents on hepatitis, but beyond that, it may also be a reflection of direct effect of known immunological impacts of inflammation on depression and anxiety in the etiology of which inflammation is known to play a significant role. This finding requires further studies on wider sampling groups.
Kronik hepatit B hastalarında hastalık süresi, evresi ve tedavisinin depresyon ve anksiyete ilişkisi
Keywords: chronic hepatitis B; depression; anxiety; treatment